Evil Mothers. From Devouring Witches to Deadly Ghosts - Tausiet, María (Amaltea. Journal of Myth Criticism, 2019)
Since time immemorial, the figure of the mother has sparked ambivalent emotional reactions, ranging from adoration to deep-rooted fear. The myth of the child-killing woman was materialized during the Early Modern Age in the classic witch. The transformation of the myth of the evil mother from devouring witch to deadly ghost occurred in Europe during the Enlightenment and the early Romantic era. Then, the traditional wicked witch mother adopted a guise that was considerably more ambiguous and subtle, though no less threatening: that of the dominant mother who might not physically eliminate her children but nonetheless exerted a debilitating influence over them.